Risk and Protective Factors of Suicidal Ideation in Adolescents. (29th March 2019) - Primananda, Meulu; Keliat, Budi Anna
ABSTRACT: Suicidal ideation is commonly found among adolescents. It is influenced by both risk factors (hopelessness, depression, anxiety, and stress) and protective factors (coping, social support, and self-esteem). The aim of this study was to determine the relationship between the risk and the protective factors of suicidal ideation. This was a descriptive correlative research with a cross-sectional approach that studied 207 senior high school adolescents. These adolescents filled out questionnaires related to suicidal ideation, risk factors, and protective factors. The data analyses conducted were univariate and bivariate analyses. The risk factors hopelessness, depression, anxiety, and stress are found to be associated with high suicidal ideation. This study also found that coping, social support, and self-esteem are negatively associated with suicidal ideation. The relationship between suicidal ideation and its risk and protective factors found in this study can be used to develop appropriate nursing interventions for preventing suicidal ideation in adolescents.